Creative thinking in the teaching of Chinese language and literature in colleges from the perspective of educational psychology - Zhong, Li (Frontiers in Psychology, 2022)
In the major of Chinese language and literature, the reading of Chinese language and literature is the most basic part. With the development of internet technology, the teaching of Chinese language and literature has also ushered in new changes. In order to better innovate the teaching methods of Chinese language and literature education according to the emerging internet technology, this study applies the scaffolding teaching model based on educational psychology to Chinese language teaching. Firstly, the educational psychology and scaffolding teaching theory are analyzed, and a scaffolding teaching model of educational psychology is proposed. Secondly, this model is applied to the teaching of Chinese language and literature majors in colleges, and teaching experiments are carried out. The results show that the Chinese language and literature reading anxiety of the students in the experimental class has been alleviated to a certain extent. After using the scaffolding teaching model based on human-computer interaction and educational psychology to conduct teaching experiments, the average reading anxiety of the experimental class is 67.13 points, and the average reading anxiety of the control class is about 76.52 points. The average post-test reading anxiety of the experimental class is 9.39 points lower than that of the control class. The students’ Chinese language and literature scores improve after the experiment. Therefore, the scaffolding teaching model based on educational psychology can be used in the teaching of Chinese language and literature majors in colleges and universities. This study can realize the effective teaching inside and outside the classroom of Chinese language and literature in colleges and universities, promote the deep integration of educational psychology and the teaching of Chinese language and literature, and provide a new teaching idea for Chinese language and literature teachers.